Fibrin Glue Closure for Intractable Pancreatic Fistulae after Pancreaticoduodenectomy - Okamoto, Kojun; Koyama, Isamu; Hara, Kiyoka; Aikawa, Masayasu; Okada, Katsuya; Watanabe, Yukihiro; Miyazawa, Mitsuo (JOP. Journal of the Pancreas, 2015)
Context Treatment of pancreatic fistulae after pancreaticoduodenectomy is extremely important because it determines the patient's postoperative course. In particular, treatment of grade B cases should be conducted in a timely manner to avoid deterioration to grade C. Objective We report the successful treatment of six cases of postoperative intractable, grade B pancreatic fistulae, in which fistula closure was achieved through the use of tissue adhesive. Methods Six subjects presented at our hospital with grade B pancreatic fistulae after pancreaticoduodenectomy. In all cases, the drain amylase values were high immediately after the operation, and the replacement of the drain was enforced. Closure of the fistula was performed by pouring tissue adhesive into the fistula from the drain, after the fistula had been straightened. Results Closure of the fistula was achieved in all six cases at the first attempt. The average fistula length was 13.2 cm, the average volume of pancreatic fluid discharge just before treatment was 63.3 mL, the average amylase value in the drainage was 40,338.5 IU/L, and the subjects were discharged from hospital an average of 8.8 days after treatment. There were no recurrences after treatment. Conclusion Intractable pancreatic fistulae can be effectively treated using the tissue adhesive method. Image: Pancreatic fluid drainage.